Manajemen Perioperatif pada Pasien dengan Sindrom Brugada - Kurniawaty, Juni; Widyastuti, Yunita; Ridha, Ihsanur (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
Background: Brugada syndrome is a congenital disease characterized by Right Bundle Branch Block(RBBB) with an increase in the ST segment in the right precordial sadapans and is associated with suddendeath and lethal arrhythmias. Brugada syndrome is reported to be responsible for 4% of all sudden deaths and 20% of sudden deaths in those who do not suffer from structural heart disease and is the sadapaning cause of death in subjects under the age of 40 years. We reported a 40 years-old man with diagnosis of SO Filled Eye OD and was planned to underwent an OD Evacuation SO. There was Brugada ECG type 2 in this patient without any history and clinical symptoms of Brugada. Anesthesia was carried out with GA LMA Supreme No. 4 and induction of anesthesia with Sevoflurane inhalation agents. Monitoring during operations with 5 sadapan ECGs, NIBP, SpO2 and IOC. Patient’s hemodynamics during surgery was managed to be stable without any turmoil that can cause arrhythmias and VT VF. After the operation, monitoring in the recovery room was carried out for 4 hours and after being stabilized returned to the ward.